A place called perfect / They've got their eyes on you - Duggan, Helena (London : Usborne., 2017)
Violet never wanted to move to Perfect. Who wants to live in a town where everyone has to wear glasses to stop them going blind? And who wants to be neat and tidy and perfectly behaved all the time? Violet quickly discovers there's something weird going on in the town - she keeps hearing voices, her mam is acting strange and her dad has disappeared. When she meets Boy she realizes that her dad is not the only person to have vanished ... and that the mysterious Watchers are guarding a perfectly creepy secret!
M
b
b